Perbedaan Pengetahuan Ibu Dalam Penanganan Pertama Kejang Demam Pada Anak Balita Sebelum dan Setelah Diberikan Edukasi Dengan Media Leaflet - Erliawati, Putu Nevi; Suarniti, Ni Wayan; Armini, Ni Wayan (JURNAL MEDIKA USADA, 2025)
Febrile seizure is a situation when a child experiences a seizure attack due to a body temperature that rises above 38°C which does not occur due to problems in the skull. If febrile seizures are not resolved properly, it has an impact on the inhibition of the brain development process, paralysis, mental retardation, and 2-10% can develop into epilepsy and even die. This study is aimed at understanding the differences in mothers knowledge regarding the first treatment of febrile seizures in children under five before and after being educated through leaflet media. The type of pre-experimental research used one group pretest-posttest design through purposive sampling techniques. The research was carried out in October 2024 at the Sakura Ward of Buleleng Regency Hospital which had a total sample of 32 people. The results of the pre-test were obtained that the majority of respondents had a low level of knowledge, which was 90.6%. The results of the post-test were obtained that the majority of respondents had a good level of knowledge, which was 93.8%. The results of the research through testing using the paired t-test statistical test, a value of p = 0.000 was obtained. Because the value of p < α 0.05, H0 is rejected Ha is accepted. It can be concluded that there is a difference in mothers knowledge regarding the first treatment of febrile seizures in children under five before and after being educated through leaflet media at the Sakura Ward of Buleleng Regency Hospital. Therefore, health workers are expected to be able to use leaflet media in delivering education in a short, concise and clear manner, so that the dissemination of information related to the prevention of fever seizures in toddlers runs effectively and efficiently.